"They can't take a trade off you" - varying perceptions of job security over 50 years at the Midland Government Railway Workshops - Oliver, Bobbie (Australian Society for the Study of Labour History, 2007)
The Government Railway Workshops at Midland closed in 1994, after a 90-year history as Western Australia's largest industrial factory. Long before the closure, however, the Workshops had ceased to be a place of permanent, lifetime employment for many of the apprentices who trained there. Over a decade after the Workshops' closure, Western Australia (like the rest of the nation) was suffering an acute shortage of skilled labour, requiring such government strategies as programs to attract skilled immigrants (reminiscent of the 1950s), and developing a 'Fast Track' Apprentice training program as well as 'short training courses' to alleviate the problem.This paper, firstly, analyses the changing perceptions of a skilled trade in the second half of the twentieth century, in the context of the Midland Government Railway Workshops. Then, it examines the climate of change that contributed to the Workshops' closure in 1994, and discusses some of its impacts. The paper concludes by examining the human cost of the closure, and attempting to assess some of the longer-term impacts, particularly with regard to providing training for trades apprentices and maintaining a skilled workforce in the State of Western Australia.